KEBIJAKAN PENGELOLAAN PERTAMBANGAN BATUBARA PADA NEGARA AMERIKA, CINA, INDONESIA (Studi Normatif dan Perbandingannya) - Aullia Vivi Yulianingrum; Sunariyo Sunariyo; Bayu Prasetyo (Jurnal Ilmiah Advokasi, 2022)
This article aims to describe how is the policy of coal mining management on country which its system is socialism or capitalism then it will be compared with coal mining management policy in Indonesia that follow democracy system. This research is included ad qualitative research. The method used is literature study which to find the policy that is used by a country that follow capitalism, socialism, and Islam ideologies. By the case approach that law regulations are found in every country which has function for legal reform or the founding of law fundamentals in Indonesia. The data used is secondary data and it is analyzed with logical deduction. Chinese and United States of America in formulating their mining management policies, they are more emphasizing on workers’ protection or safety regulations. Indonesia in mining management accommodates policies regarding occupational safety, however the environmental is not accompanied by linkages and integration of regulation nuances, then inequality and contradictive are happened along with conflict in those policies formulation. Mining management policies include the regulations of environmental management, to preserve nature and harmonize nature not only gives priority on workers safety.Keywords: Policy, Coal Mining, Comparative Law